2010
DOI: 10.1002/uog.7689
|View full text |Cite
|
Sign up to set email alerts
|

Value of transvaginal ultrasound in assessing severity of pelvic endometriosis

Abstract: Objective The objective of this study was to examine the ability of preoperative transvaginal ultrasound (TVS) scanning to assess the severity of pelvic endometriosis. 62/201 (30.8%; 95% CI, whereas 33/201 (16.4%; 95% CI, 31/201 (15.4%; 95% CI, 27/201 (13.4%; 95% CI, 95% CI,2) had severe endometriosis. The sensitivity and specificity of the TVS diagnosis of severe pelvic endometriosis were 0.85 (95% CI,, respectively, and the positive and negative likelihood ratios were 43.5 (95% CI, Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 31 publications
(39 reference statements)
10
98
2
1
Order By: Relevance
“…Therefore, in women who are infertile or have chronic pelvic pain, and in the absence of ovarian endometriomas, it is important to look for sonographic signs of adhesions. Only a few studies have attempted to assess the ability of transvaginal sonographic examination to detect the presence of pelvic adhesions in women with pelvic endometriosis, and to assess their severity [32][33][34][35].…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…Therefore, in women who are infertile or have chronic pelvic pain, and in the absence of ovarian endometriomas, it is important to look for sonographic signs of adhesions. Only a few studies have attempted to assess the ability of transvaginal sonographic examination to detect the presence of pelvic adhesions in women with pelvic endometriosis, and to assess their severity [32][33][34][35].…”
Section: Ultrasound Evaluationmentioning
confidence: 99%
“…TVS has the ability to diagnostic ovarian endometriomas and to detect presence of pelvic endometriosis affecting the pouch of Douglas, recto-vaginal space, sacro-uterine ligaments and recto-sigmoid colon. Recent studies have shown that the accuracy of TVS in the detection of deep infiltrating endometriosis is about 90%, with a sensitivity of 81-85% and a specificity of 94-98% [28,29].…”
Section: Endometriosis Groupmentioning
confidence: 99%
“…In addition to endometriomas, expert operators can accurately map endometriosis including rectovaginal nodules and bowel nodules. Coupled with an assessment of pelvic organ mobility, it is now possible to reliably diagnose advanced endometriosis on ultrasound [7,8]. This information can be used to reduce the need for diagnostic laparoscopy and accelerate appropriate treatment for patients.…”
Section: Workupmentioning
confidence: 99%